Beberapa Faktor Risiko Lingkungan yang Berhubungan dengan Kejadian Malaria di Kecamatan Nanga Ella Hilir Kabupaten Melawi Provinsi Kalimantan Barat. - Ristadeli, Theresia; Suhartono, Suhartono; Suwondo, Ari (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background : Malaria is an infectious disease caused by a Plasmodium parasite. This disease is transmitted by biting of infected female Anopheles sp mosquitos. Inside human body, the parasite lives in a heart and infects red blood cells. Melawi District is an endemic area of Malaria. Annual Malaria Incidence (AMI) is an indicator to describe all occurrences of clinical Malaria at a region. At Sub district of Nanga Ella Hillir in District of Melawi, AMI in 2008 was 67.31 per 1000 citizens, in 2009 was 50.01 per 1000 citizens, and in 2010 was 73.99 per 1000 citizens. It means AMI increased from 2008 to 2010. The objective of this research was to analyze some environmental risk factors related to the occurrence of Malaria at Nanga Ella Hilir Sub District, Melawi District, Province of West Kalimantan. Methods : This was an observational research with a case control approach. Number of samples was 68 respondents for case group and 68 respondents for control group. Data were analyzed using the methods of univariate, bivariate (Chi-Square test and Odds Ratio), and multivariate (Logistic Regression test). Result : The result of bivariate analysis showed that the variables as risk factors to the occurrence of Malaria were: unvailability of wire netting at ventilation (p:0.001; OR: 10.5 (95% CI: 3.4 – 32.3)), availability of pond (p: 0.016; OR: 2.5 (95% CI : 1.3 – 4.9), availability of bush at surrounding a house (p: 0.026 ; OR: 5.4 (95% CI: 2.5-11.4)), availability of livestock (p:0.001; OR: 4.0 (95%CI: 2.0-8.3)), availability of stagnant water (p=0.009; OR: 2.7 (95% CI: 1.3-5.4)), habit of installing mosquito net (p: 0.017; OR: 2.6 (95%CI: 1.2-5.5)), and custom to go outdoors at night (p:0.001; OR: 5.2 (95%CI: 2.4 – 11.1)). In addition, multivariate analysis showed that probability of a person to suffer from Malaria at the conditions: no wire netting at ventilation, any pond around a house, any livestock, any stagnant water, no mosquito net, and any habit to go outdoors at night is approximately equal to 71%. Key Words : Malaria, Environmental Risk Factors, Nanga Ella Hilir, Melawi District